APLIKASI GAME PETUALANGAN “ENYONG KENCOT” MENGGUNAKAN CONSTRUCT 2 BERBASIS ANDROID - Dwi Farizki, Kukuh; Hartono, Budi (Information Technology and Telematics, 2018)
Abstract Enyong Kencot is an adventure platformer game where the Enyong will adventure after school, down the obstacles while collecting snacks and food. This game is inspired by the desire to introduce Purbalingga's unique cuisine to children through smartphone games. Players must play as enyong and look for 3 food items at each level. After getting 3 pieces of food, the star item will appear. After the player takes a star, the player must answer questions about Purbalingga's typical food and if they are correct they will get a snack bonus and food info. Snacks are collected as much as possible in order to achieve the highest score.